Fintech in a flash : financial technology made easy - Rubini, Agustín (De'G Press, 2019)
"The financial services technology industry is booming and promises to change the way we manage our money online, disrupting the current landscape of the industry. Understanding fintech's many facets is the key to navigating the complex nuances of this global industry. Fintech in a Flash is a comprehensive guide to the future of banking and insurance. It discusses an array of hot topics such as online payments, crowdfunding, challenger banks, online insurance, digital lending, big data, and digital commerce. The author provides easy to understand explanations of the 14 main areas of fintech and their future, and insight into the main fintech hubs in the world and the so-called unicorns, fintech firms that have made it past a $1 billion valuation. He breaks down the key concepts of fFintech in a way that will help you understand every aspect so that you can take advantage of new technologies. This detailed guide is your go-to source for everything you need to confidently navigate the ever-changing scene of this booming industry."- Resumé vydavatel
Keywords: finanční služby; inovace; informační technologie; banky; bankovnictví; crowdfunding; financial services industry; innovations; information technology; banks; banking; elektronické knihy; monografie; electronic books; monographs